Development Of Smart Dental Mirror Based On Light Sensor And The Effectiveness Of Its Application On The Quality Of Examination - Cici Idela; Bedjo Santoso; Lanny Sunarjo (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2026)
A common problem faced by dentists and dental therapists when using a conventional dental mirror is the need for additional light, such as a flashlight or headlamp, to perform examinations on patients, thereby reducing the effectiveness and efficiency of the examination process. The purpose of this research is to produce innovative tools and analyze their effectiveness to assess the quality of the examination in the aspects of simplicity, safety, efficiency, and accuracy. This research uses the Research and Development (R&D) method with stages: information gathering, product development design, expert validation, product trials, and product results. Sampling totaled 33, consisting of 3 experts and 30 respondents from dental and oral health workers. The independent variable is the Smart Dental Mirror tool. The research data were tested using a Likert Scale and SPSS program analysis Wilcoxon Signed Rank Test. The results of this study are that the Smart Dental Mirror is feasible, with the results of testing by experts using a Likert Scale of 93.05%. The results of the effectiveness test of using Smart Dental Mirror show a value of entirely at 0.000 (p <0.05) in the aspects of simplicity, safety, efficiency, and accuracy.